(untitled) (Revista Brasileira Multidisciplinar, 2020)
COVID-19 is an infectious disease that has spread rapidly around the world, characterizing a pandemic. Its etiologic agent is SARS-CoV-2, which promotes respiratory infections, mainly with symptoms equivalent to the common cold, but also complications, especially in patients with comorbidities. So far, there are no reports of medication, available to the population, capable of controlling the proliferation of the virus. In this context, an alternative that emerges and is also being discussed is the use of convalescent plasma (CP). Therefore, this study aimed to present a possible therapeutic resource for the care of patients infected with SARS-CoV-2 using CP, based on evidences from the literature. To achieve this goal, databases, such as Google Scholar, Scielo, Science Direct and PubMed, were used to search for evidences. Among the keywords used can be mentioned: “Coronavirus”, “COVID-19”, “SARS-CoV-2”, “convalescent plasma” isolated or in combination. The CP consists of plasma from patients who have already had the disease and recovered, serving as a source of specific antibodies of human origin, since there was the development of humoral immunization against the infectious agent. Therefore, in this case, the intention is to perform a CP transfusion for patients who are sick, neutralizing the pathogen and eventually leading to its eradication of blood circulation, since the antibody circulates in the blood, reaches tissues and protects against infections. There are not many studies available in the literature on the topic yet, but they already show promising results, including those associated with previous evidence of other viral infections such as Ebola, H5N1, H1N1 and measles. It is concluded that convalescent plasma may be a potential therapy for patients infected with SARS-CoV-2 with the highest risk involved. Serious adverse reactions associated with the use of CP have not been described, but an improvement in the condition compared to no treatment.